SOCIAL AND ECONOMIC DEVELOPMENT OF MAGADAN: FROM A PLANNED ECONOMY TO A MARKET ECONOMY (1960–2020) - Natalya V. Galtseva; Oksana S. Favstritskaya; Olga A. Sharypova (Север и рынок: формирование экономического порядка)
The development of Russian northern cities and their unique transformation during the post-Soviet period present a compelling subject for research in terms of identifying both general trends and differences. Although northern cities are relatively younger than their central and southern counterparts, they serve as strategic hubs for the development of critical territories, including the Arctic. One such city is Magadan, located in the Russian Far East. This research provides a comprehensive analysis of the key economic sectors in Magadan, evaluating management practices and the effectiveness of government support under distinct economic systems from 1960 to 2020. The study aims to assess the socio-economic development of Magadan and identify the main factors influencing its trajectory under both planned and market economies. A combination of historical, economic, statistical, and comparative analyses was employed, alongside visualization and elements of systems analysis. Archival data from 1960–1990, characterizing the city’s socio-economic development, were examined and are now introduced into scientific discourse for the first time. The findings reveal that during the planned economy era, Magadan experienced major growth, with integrated development across industries, population increase, and economic appeal driven by northern benefits provided by the government. In contrast, the market economy era saw economic contraction, reduced living standards compared to the national average, and migration shifts, including a population decline both regionally and within the city itself. Magadan transitioned from a dynamically growing city under the planned economy to a declining one under market conditions. The primary drivers of these changes were shifts in management principles and the diminishing effectiveness of northern benefits as a policy tool. The results of this study have implications for developing socio-economic strategies and government programs supporting northern and northeastern cities. Future research will focus on identifying a viable “smart shrinking” model to address these challenges.